Crosstalk between neuroinflammation and oxidative stress in epilepsy - Fabisiak, Timothy; Patel, Manisha (Frontiers in Cell and Developmental Biology, 2022)
The roles of both neuroinflammation and oxidative stress in the pathophysiology of epilepsy have begun to receive considerable attention in recent years. However, these concepts are predominantly studied as separate entities despite the evidence that neuroinflammatory and redox-based signaling cascades have significant crosstalk. Oxidative post-translational modifications have been demonstrated to directly influence the function of key neuroinflammatory mediators. Neuroinflammation can further be controlled on the transcriptional level as the transcriptional regulators NF-KB and nrf2 are activated by reactive oxygen species. Further, neuroinflammation can induce the increased expression and activity of NADPH oxidase, leading to a highly oxidative environment. These factors additionally influence mitochondria function and the metabolic status of neurons and glia, which are already metabolically stressed in epilepsy. Given the implication of this relationship to disease pathology, this review explores the numerous mechanisms by which neuroinflammation and oxidative stress influence one another in the context of epilepsy. We further examine the efficacy of treatments targeting oxidative stress and redox regulation in animal and human epilepsies in the literature that warrant further investigation. Treatment approaches aimed at rectifying oxidative stress and aberrant redox signaling may enable control of neuroinflammation and improve patient outcomes.